The Relationship Between Macroeconomic Variables, LPS Guarantee Interest Rate, and Time Deposit Collection in Conventional Banks in Indonesia from 2005 to 2024 - Yoka, Teofilus; Harsono, Ricky Dwi Budi (Dinasti Publisher, 2025)
This study presents empirical evidence of the relationship between macroeconomic indicators - gross domestic product, inflation, and the rupiah exchange rate against the US dollar - and the LPS guarantee interest rate with time deposit funds collected by conventional banks - commercial banks and rural banks - in Indonesia during 2005–2024. The ordinary linear regression (OLS) model with secondary data documented from the Financial Services Authority and the Central Statistics Agency significantly explains the variation in time deposit funds. Partially, the exchange rate has a significant positive relationship, while the LPS guarantee interest rate has a significant negative relationship, with time deposit funds. It is concluded that customers of commercial banks and rural banks in Indonesia consider exchange rate stability and security of savings in depositing their funds.